Enzymatic regioselective and complete deacetylation of two arabinonucleosides - Sabaini, María Belén; Zinni, María A.; Mohorčič, Martina; Friedrich, Jožefa; Iribarren, Adolfo Marcelo; Iglesias, Luis Emilio (Journal of Molecular Catalysis B: Enzymatic)
Candida antarctica lipase B (CAL-B)-catalysed regioselective deacetylation of 2′,3′,5′-tri- O-acetyl-1-β- d-arabinofuranosyluracil (1) and 2′,3′,5′-tri- O-acetyl-9-β- d-arabinofuranosyladenine (2) was studied. The choice of the reaction medium allowed the regioselective formation of products bearing different degree of acetylation: in isopropanol, CAL-B catalysed the formation of the corresponding 2′- O-acetylated arabinonucleosides, while hydrolyses afforded the 2′,3′-di- O-acetylated products. In particular, the procedure herein described allows a simple and efficient preparation of the reported vidarabine prodrug 2′,3′-di- O-acetyl-9-β- d-arabinofuranosyladenine, avoiding the utilisation of protective groups. Moreover, to achieve full deacetylation of the assayed substrates, a set of commercial hydrolases and fungal keratinases from Doratomyces microsporus (DMK) and Paecilomyces marquandii (PMK) were tested. While only PMK and DMK catalysed the quantitative complete deacetylation of 1, DMK accomplished full deacetylation of 2 in shorter time than the other assayed enzymes. Fil: Sabaini, María Belén. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina Fil: Zinni, María A. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina Fil: Mohorčič, Martina. National Institute Of Chemistry; Eslovenia Fil: Friedrich, Jožefa. National Institute Of Chemistry; Eslovenia Fil: Iribarren, Adolfo Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina Fil: Iglesias, Luis Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina